2016
DOI: 10.1021/acs.jmedchem.6b00784
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro and in Vivo Anti-Trypanosoma cruzi Activity of New Arylamine Mannich Base-Type Derivatives

Abstract: ABSTRACT. Chagas disease is a neglected tropical disease with 6-7 million people infected worldwide and there is no effective treatment. Therefore, there is an urgent need to continue researching in order to discover novel therapeutic alternatives. We present a series of arylaminoketone derivatives as means of identifying new drugs to treat Chagas disease in the acute phase with greater activity, less toxicity and with a larger spectrum of action than that corresponding to the reference drug benznidazole. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 67 publications
2
47
0
Order By: Relevance
“…The in vivo acute model showed that the compounds decrease the parasitemia from the beginning of the treatment and parasites were not detected from day 25 post-infection. Moreover, none of the compounds showed reactivation after immunosuppression with the dose used with the reference drug (100 mg/kg) and the lead compounds showed no reactivation also at 50 mg/kg [3].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The in vivo acute model showed that the compounds decrease the parasitemia from the beginning of the treatment and parasites were not detected from day 25 post-infection. Moreover, none of the compounds showed reactivation after immunosuppression with the dose used with the reference drug (100 mg/kg) and the lead compounds showed no reactivation also at 50 mg/kg [3].…”
mentioning
confidence: 92%
“…The in vivo acute model showed that the compounds decrease the parasitemia from the beginning of the treatment and parasites were not detected from day 25 post-infection. Moreover, none of the compounds showed reactivation after immunosuppression with the dose used with the reference drug (100 mg/kg) and the lead compounds showed no reactivation also at 50 mg/kg [3].Considering the in vivo results, three out of four derivatives were selected for their mutagenicity evaluation and were non-mutagenic in the Ames test. Moreover, the absorption, distribution, metabolism, and excretion (ADME)/Tox and Pharmacokinetic (PK) evaluations are ongoing and the results will be presented in this congress.…”
mentioning
confidence: 99%
“…Therefore, we design and synthesize new potential inhibitors against these two targets for the therapy of CD [6]. In this context, we carried out a docking study of a new series of imidazole-based derivatives with the ability to inhibit these two exclusive targets that regulate T. cruzi redox metabolism.…”
mentioning
confidence: 99%
“…Governmental and non-governmental organizations have proposed big challenges with the commitment to meet the needs of these patients. One of the most important challenges is the search for new, safe, effective and affordable drugs to combat these diseases as the current therapeutic arsenal is inadequate and insufficient [2].In this context, our research group has been working on the discovery of new Mannich base-type derivative compounds as promising molecules for new anti-trypanosomatid agents [3].Considering the target product profile of these diseases and the results found to date, we persist in the search of potentially trypanocidal compounds; therefore, thirty-three new derivatives have been synthesized by different, simple and cheap synthetic routes.All compounds have been tested in vitro against the epimastigote form in three different T. cruzi strains (SN3, Arequipa and Tulahuen) for Chagas disease and in the promastigote form in L. braziliensis, L. donovani and L. infantum. The cytotoxicity has also been determined using Vero and THP-1 mammalian cell lines to establish their selectivity index (SI).…”
mentioning
confidence: 99%
“…In this context, our research group has been working on the discovery of new Mannich base-type derivative compounds as promising molecules for new anti-trypanosomatid agents [3].…”
mentioning
confidence: 99%